Implementasi Pengenalan Gizi Seimbang Anak Melalui Kreasi Bentuk Makanan - Rianti Rianti; Ayu Kholifah; Latipatul Hasanah; Titing Setiasih (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
Creation of food forms is an activity that is used to make it easier to serve food that is healthy for children, unique and creative forms of food make children interested in consuming these foods. This study aims to find out how to increase children's awareness to want to consume food with balanced nutrition through the creation of food forms and to find out whether the creation of food forms can improve children's understanding of balanced nutrition. This study uses a qualitative method. Data collection techniques used are observation and documentation techniques. The results showed that the creation of food forms was very effective in increasing children's understanding of balanced nutrition. Provisions or dishes that are created with a healthy menu consisting of foods that contain balanced nutrition can provide children with an understanding to consume healthier foods and avoid foods that can have a negative impact on health. In addition, the implementation of the introduction of balanced nutrition through the creation of food forms shows a good impact on the development and growth of children.